Towards Automatic Blocking of Shapes using Evolutionary Algorithm. (March 2020) - Lim, Chi Wan; Yin, Xiaofeng; Zhang, Tianyou; Selvaraj, Senthil Kumar; Su, Yi; Goh, Chi-Keong; Moreno, Alejandro; Shahpar, Shahrokh
Abstract: This work focuses on the use of evolutionary algorithm to perform automatic blocking of a 2D manifold. The goal of such a blocking process is to completely partition a 2D region into a set of conforming and non-intersecting quadrilaterals to facilitate the generation of an all-quadrilateral, or more preferably an ideal quadrilateral mesh configuration covering the closed 2D region. However, depending on the input shape, the optimal blocking strategy is often unclear and can be very user-dependent. In this work, a novel approach based on evolutionary algorithm is adapted to search for a potential set of such ideal configurations. Based on a selection within a set of candidate vertices from a pre-computed pool, blocking configurations can be derived and ranked based on the collective quality of its blocks. The quality of a block is computed based on objective functions relating to its interior angles and opposite length ratios. Using multi-dimensional ranking criteria, inferior solutions can be slowly filtered away with each successive generation. Based on observations on a range of turbomachinery test cases, it is possible to derive and improve near-optimal blocking configurations by utilizing a large number of generations. Highlights: A methodology to perform automatic blocking of 2D manifold shapes using evolutionary algorithm is proposed. Carefully selected candidate points optimize the chances of getting good quality solutions. Results on test cases have shown it is possible to derive sets of near-optimal blocking configurations, comparable with cross-field approaches.